Comparison Of The Effectiveness Of The 2013 Curriculum And The Independent Curriculum In History Subjects At Sman 2 Dompu - Sulaiman, Sulaiman; Sumiyati, Sumiyati; Julita, Putri; Putri, Sakila (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The objective of this study is to ascertain whether there are any notable differences in the perceptions of the effectiveness of the 2013 curriculum and the independent curriculum held by teachers. This research is qualitative in nature and employs a phenomenological study approach. The data was obtained from two sources: primary and secondary. The primary data was gathered through interviews with history subject teachers. Secondary data is obtained from written documentation, including notes from observations and interviews, as well as photographs, sound recordings, and other relevant materials. In this study, data were collected through observation, interviews, and document analysis. The data analysis in this research is conducted through the following stages: data collection, data reduction, data presentation, and conclusion drawing or verification. Validity is ensured through credibility and triangulation tests. The results of interviews with X and XI grade history education subject teachers indicate that the Merdeka Curriculum greatly facilitates the learning process. This is because, with an independent curriculum, learning is not only student-centred, allowing for the improvement of abilities, but also affords teachers the freedom to design and implement educational plans. Students are afforded the opportunity to select their areas of interest, thereby alleviating the academic burden and fostering pedagogical creativity among instructors.